UPAYA PENINGKATAN KUALITAS PEMBELAJARAN PADA MASA PANDEMI COVID-19 DI BANDUNG BARAT - Abdul Mun'im Amaly (Jurnal Al Maesarah, 2022)
The Covid-19 pandemic poses a major obstacle in the world of education, especially in the online learning process in schools, coupled with the phenomenon that not all citizens have media for online learning so that the quality of learning has decreased. Therefore, community service seeks to improve the quality of learning during the Covid-19 pandemic so that the expected results can be achieved. The method used is expository, which is to go directly to the community by applying various efforts such as learning assistance, adding media, and providing motivation. The results of this study indicate that after various efforts have been made, such as learning assistance, adding media, and providing motivation, students can understand learning better, which means that there is an increase in the quality of learning.